A reflection on architectural design methodologies - Kowaltowski, Doris Catharine Cornelie Knatz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper discusses architectural design methods in view of the present day complexities of the creative process, technological advances and social and economic changes. This scenario demands a change in attitude and the application of more systematic procedures during the design process. Various design methods are presented which discuss the synthesis, analysis and evaluation of the important architectural factors. The potential of these methods are shown. Techniques and procedures for building performance assessment, design evaluation, and drawing and drafting are presented, as well as the use of physical and virtual models. Thus, the paper reflects upon the ways and means of how architects organize the search for high quality design solutions which satisfy human needs.